BIAYA DAN KEUNTUNGAN PEMASARAN IKAN PATIN BUDIDAYA - M Ramli (Berkala Perikanan Terubuk, 2009)
This Paper is result survey patin fish (Pangasius' sutchi) marketingKampar district origin to Rantauprapat. Aim survey to see cost magnitude, profitand marketing efficiency. Result survey known marketing cost for Kampar districtcollectors tradesman as big as 96,51% from total revenue, for wholesaler andRantauprapat's retailer each of 91,51% and 92,58% from total revenue. Biggestcost lays in transportation cost from Kampar district to Rantauprapat. Collectorstradesman marketing cost to every fish kilogram as big as Rp 10.616,00, pricesells Rp 11.000,00 and profit as big as Rp 384,00. Wholesaler marketing cost toevery fish kilogram as big as Rp 11.440,00, price sells Rp 12.500,00 and profit asbig as Rp 1.060,00. Retailer marketing cost to every fish kilogram as big as Rp12.960,00, price sells Rp 14.000,00 and profit as big as Rp 1.040,00. Patin fishmarketing from Kampar district to Rantau prapat still efficient.